An Ecological Perspective on Reading Development: a Theoretical Framework to Guide Empirical Research - Nadori, Neirouz (Yayasan Visi Intan Permata, 2020)
Recent efforts have addressed the new challenges related to conceptualizing, understanding and improving reading competency. Several literacy researchers have perceived reading as a developmental skill that is not situated exclusively within student’s cognition, or within family processes, or within classroom or school processes. Rather, reading development has been viewed as a result of the dynamic interaction among reader, family, classroom, and school system (Jaeger, 2017). Following on from this, systems theory approach and more specifically the ecological model allows for the examination of reading skill development from a holistic perspective. It provides an inclusive frame for describing and explaining how the educational opportunities are distributed at the micro, meso, exo, and macro systems and how these systems interact to explain students’ reading differences amon. It also delineates how developing readers’ individual characteristics transact with both proximal and distal processes to craft their reading ecologies. Future policy, practice and research are recommended to be based on the ecological model premises to have a comprehensive view of reading development.